Optimization of Linear Functions at the Vertices of a Permutation Polyhedron with Additional Linear Constraints - Valuiskaya, O. A.; Yakovlev, S. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We propose an approximate polynomial method that enables one to determine with given accuracy the extremum of a function on a permutation polyhedron with additional linear constraints.